The Current Condition of Indonesian Literature Teachers: A Study about Student’s Constraints in Learning Writing Creative Literature - M Firdaus; Yohannes Telaumbanua (Universitas Negeri Padang, 2018)
As prospective teachers, the students of the Indonesian Language and Literature Education Study Program must have sufficient literary skills and experience of writing literature works. The facts are, however, very different. To date, most students face varied kinds of obstacles to writing literature works. Writing literature works require lofty creativity and imagination to produce the Dulce Et Utile (radiating the beam of the aesthetic and educational values of the works). The purpose of this study was, therefore, to describe the factors that become the students’ major obstacles to writing literature works. The method used was the qualitative descriptive whilst the observation, interview, and document analyses were the techniques of data collections. The 21 subjects of this study were the sixth-semester students of undergraduate Indonesian Language and Literature major at the Islamic University of Riau (UIR). The results of this study indicated that the factors that become the students’ crucial obstacles to learning Writing Literature Works were the lecturers’ unprofessionalism (centered-staged with different discipline/area of study of lecturers), lack of respect to the Writing Literature Works’ course; limited number of credit course, continue transmitting theoretical knowledge rather than keep practicing/writing the works, and the inappropriate teaching/learning model used in the Writing Literature Works’ course. As a result, these factors is a form of the implementation of learning writing literature works is still a formality and certainly prevent the students of being professional teachers.